Repurposing and Revival of the Drugs: A New Approach to Combat the Drug Resistant Tuberculosis - Sharma, Divakar; Dhuriya, Yogesh K.; Deo, Nirmala; Bisht, Deepa (Frontiers in Microbiology, 2017)
Emergence of drug resistant tuberculosis like multi drug resistant tuberculosis (MDR-TB), extensively drug-resistant tuberculosis (XDR-TB) and totally drug resistant tuberculosis (TDR-TB) has created a new challenge to fight against these bad bugs of M.tuberculosis. Repurposing and revival of the drugs are the new trends/options to combat these worsen situations of tuberculosis in the antibiotics resistance era or in the situation of global emergency. Bactericidal and synergistic effect of repurposed/revived drugs along with the latest drugs bedaquiline and delamanid used in the treatment of MDR-TB, XDR-TB and TDR-TB might be the choice for future promising combinatorial chemotherapy against these bad bugs.